Adherence to medical follow‐up recommendations reduces hospital admissions: Evidence from diabetic patients in France. (21st January 2020) - Bussière, Clémence; Sirven, Nicolas; Rapp, Thomas; Sevilla‐Dedieu, Christine
Abstract: The aim of this study was to document the extent to which diabetic patients who adhered to required medical follow‐ups in France experienced reduced hospital admissions over time. The main assumption was that enhanced monitoring and follow‐up of diabetic patients in the primary care setting could be a substitute for hospital use. Using longitudinal claim data of diabetic patients between 2010 and 2015 from MGEN, a leading mutuelle insurance company in France, we estimated a dynamic logit model with lagged measures of the quality of adherence to eight medical follow‐up recommendations. This model allowed us to disentangle follow‐up care in hospitals from other forms of inpatient care that could occur simultaneously. We found that a higher adherence to medical guidance is associated with a lower probability of hospitalization and that the take‐up of each of the eight recommendations may help reduce the rates of hospital admission. The reasons for the variation in patient adherence and implications for health policy are discussed.